COMPARATIVE ASSESSMENT OF THE CHARACTERISTICS OF WOMEN WITH BENIGN UTERINE PATHOLOGIES AND REPRODUCTIVE DISORDERS - Huseynova, Z.S. (World of Medicine and Biology, 2025)
Menorrhagic disorders of menstrual function predominated in the group with uterine fibroids (51.5 %), metrorrhagic disorders in the group with endometrial polyps (60.0 %), and dysmenorrhea (42.1 %) in the group with adenomyosis (73.7 %). Primary infertility was more common in the group with endometrial polyps, occurring in 64 % of patients. Among benign uterine pathologies, secondary infertility was more prevalent in the group with endometrial hyperplasia, occurring in 58.1 % of patients. Dopplerographic parameters of the uterine arteries, especially the systolic – diastolic ratio S/D – right uterine artery – 7.28±0.44; S/D – left uterine artery – 7.51±0.41), resistance index (IR – right uterine artery – 0.851±0.011; IR – left uterine artery – 0.862±0.009) and the pycnotic index (PI – right uterine artery – 2.49±0.011; PI – left uterine artery – 2.66±0.11)., were relatively high in patients with adenomyosis. However, in patients with uterine fibroids, these indicators were lower (S/D – right uterine artery – 4.26±0.13; S/D – left uterine artery – 4.62±0.11), than in patients with other benign uterine pathologies. When comparing the results of hormonal tests, it was found that in patients with benign uterine pathologies and reproductive dysfunction, the level of estradiol in the blood was increased (in group I was 97.4±1.5 pg/ml, in group IⅠ – 98.6±1.0 pg/ml, in group IⅠⅠ – 95.5±0.6 pg/ml, in group IV – 96.0±1.3 pg/ml). However, prolactin levels in patients with adenomyosis were higher (19.9±0.9 ng/mL). The available clinical and instrumental data emphasize the fact that benign uterine pathologies can negatively affect reproductive potential, as well as the practical importance of their early diagnosis.
Keywords: benign uterine pathologies; reproductive function disorders; adenomyosis; endometrial hyperplasia; uterine fibroids; endometrial polyp; infertility; miscarriages